Síntese e estudo das propriedades fotoluminescentes e fotocatalíticas dos cristais de Ag2-2xMxWO4, (M = Mg e Zn) - Lemos, Pablo Santana (2014)
This study aimed to investigate the photoluminescence and photocatalytic properties of the alpha phase of silver tungstate ( α-Ag2WO4 ) doped with Mg and Zn (where M = Mg or Zn and x = 0; 0,01; 0,02; 0,04 ou 0,08). The crystals were synthesized by precipitation and were later heat treated in a hydrothermal system heated by microwave. The crystals were characterized structurally by X-ray diffraction, Rietveld refinement and by Raman scattering spectroscopy and absorption in the infrared region. From these characterizations was observed the formation of a single phase in all cases even for doping of 8%. The morphology was analyzed by SEM, and it was possible to observe changes in form and average particle size. Concerning the optical properties, these were investigated by ultraviolet- visible (UV-vis) electronic spectroscopy, and photoluminescence measurements at room temperature. In the case of UV-vis spectroscopy was observed that the substitution of Ag+ cations by Mg2+ can cause small changes in the optical band gap energy (Egap) of the materials. With respect to photoluminescence, no significant changes were observed in the profile of the emission band between the pure and doped materials. Finally, photocatalytic experiments were conducted with the crystals in the presence of rhodamine B. The analyzes of this experiment indicated that all samples exhibit photocatalytic activity in decolorization of the Rhodamine B. It might also be noted that all the doped samples showed a higher rate of discoloration of rhodamine B than the pure Ag2WO4. The kinetics for all reactions corresponds to a pseudo first order reaction.